Estudo genético em casais com histórico de perdas fetais recorrentes - Sestari, Sheila Janaina (2021)
Recurrent miscarriage is defined as the loss of two or more consecutive pregnancies at a gestational age of less than 20-22 weeks. It is a problem of extensive research in reproductive health and affects about 5% of couples who want pregnancy. Its etiology is complex and associated with several factors, such as genetic, endocrine, anatomical, immunological, thrombophilic, viral and bacterial infections, environmental, among others. Parental genetic causes account for a considerable proportion, especially in first trimester pregnancy losses. The aim of this study was to perform genetic analysis in couples with recurrent miscarriage in search of an association with pregnancy losses. In the cytogenetic analysis, we identified a frequency of 2.5% of structural chromosomal abnormalities (inversion and translocation) and about 17.5% of heteromorphisms. In the analysis of the C677T and A1298C polymorphisms of the MTHFR gene and I/D of the ACE gene, no significant association was identified regarding the increased risk of recurrent miscarriage in any of the evaluated polymorphisms. Regarding copy number variants (CNVs), the literature review identified 16 CNVS in 10 different chromosomes, all with potential risk for pregnancy maintenance. Thus, the positive findings for genetic alterations in this study support its association with recurrent miscarriage, as well as the importance of these analyzes for an assertive medical conduct and carrying out genetic counseling.